Applications in Awake Animal Magnetic Resonance Imaging - Ferris, Craig F. (Frontiers in Neuroscience, 2022)
There are numerous publications on methods and applications for awake functional MRI across different species e.g. voles, rabbits, cats, dogs, and rhesus macaques. Each of these species, most obviously rhesus monkey, have general or unique attributes that provide a better understanding of the human condition. However, much of the work today is done on rodents. The growing number of small bore (≤ 30 cm) high field systems 7T- 11.4T favor the use of small animals. To that point, this review is primarily focused on rodents and their many applications in awake function MRI. Applications include, pharmacological MRI, drugs of abuse, sensory evoked stimuli, brain disorders, pain, social behavior, and fear.